Characteristics of People Seeking Prescribed Cannabinoids for the Treatment of Chronic Pain: Evidence From Project Twenty 21 - Schlag, Anne Katrin; Lynskey, Michael; Fayaz, Alan; Athanasiou-Fragkouli, Alkyoni; Brandner, Brigitta; Haja, Barbara; Iveson, Elizabeth; Nutt, David J. (Frontiers in Pain Research, 2022)
Background Prescribed cannabinoids are now legal in the UK and increasingly being used for a variety of conditions, with one of the most frequent conditions being chronic pain. This paper describes the characteristics of individuals seeking prescribed cannabinoids for the treatment of chronic pain in Project Twenty 21, a UK based real world data registry of prescribed cannabis patients. Method By 1st November 2021 data were available for 1,782 people who had sought treatment with medical cannabis as part of Project Twenty 21. The most common diagnosis among this cohort was chronic pain with 949 (53.5%) of the cohort reporting a primary condition related to chronic pain. Medical and self-report data on the characteristics of these patients, their health status and type/s of cannabinoid/s prescribed are summarized in this report. Results Of the 949 people reporting chronic pain as a primary condition 54.7% were male and their average age was 42.0 years (range = 18–84). Patients reported a low quality of life and high levels of comorbidity: people reported an average of 4.6 comorbid conditions with the most common comorbid conditions including anxiety, depression, insomnia and stress. A range of cannabinoid products were prescribed with the most common products being classified as high THC flower (48.5%). The majority of patients also reported using at least one other prescribed medication (68.7%). Conclusions Consistent with findings in other national and international databases, chronic pain was the most common primary condition in this real world study of prescribed cannabinoids. There was considerable variation in the types of chronic pain, comorbid pathology and in the characteristics of products being prescribed to treat these conditions. Together, this evidence supports the utility of real world evidence, as opposed to clinical trial approaches to studying the potential benefits of prescribed cannabinoids in treating chronic pain.